A respiração das coisas : o sagrado da poesia em uma leitura da poética de Sophia de Mello Breyner Andresen - Côrtes, Ana Maria Ferreira, 1990- (2019)
Orientadores: Marcos Aparecido Lopes, Alex Villas Boas